Bosentan Does Not Affect Renal Resistive Index in Scleroderma/Systemic Sclerosis Patients - Emma Di Poi; GianLuca Colussi; Martina Bertoni; Ivan Giovannini; Barbara Tolusso; Gian Franco Ferraccioli; Elisa Gremese; Salvatore De Vita; Giulio Romano (Karger Publishers, 2023)
Introduction: If properly evaluated, chronic kidney disease can be found in up to 50% of patients with systemic sclerosis (SSc). The renal resistive index (RRI) is a marker of intrarenal vascular resistance and can predict SSc-associated vasculopathy. This study aimed to determine the impact of bosentan, a nonselective endothelin-1 receptor antagonist, on RRI and kidney function in SSc patients with recurrent digital ulcers. Methods: Twenty-one patients (age 57 ± 9 years, 19 females) were recruited in a 16-week prospective open-label uncontrolled study. Standardized procedures were used to measure general clinical and laboratory characteristics, systolic, diastolic, and mean arterial pressure (MAP), pulse pressure (PP), diastolic to systolic blood pressure (D/S) ratio, and urinary endothelin-1 levels. The Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation was used to calculate kidney function as an estimated glomerular filtration rate (eGFR). RRI was measured by Doppler ultrasound as the average of three samplings of intrarenal blood flow in different kidney regions of both kidneys. Patients with secondary causes of kidney disease or kidney diseases associated with albuminuria were excluded. Results: Bosentan treatment for 16 weeks did not change RRI (0.731 ± 0.049-0.730 ± 0.054, p = 0.925), but increased urine endothelin-1 to creatinine ratio (0.27 ± 0.15-0.49 ± 0.57 pg/mg, p = 0.032) and reduced MAP (123 ± 10-101 ± 11 mm Hg, p < 0.001), PP (76 ± 11-68 ± 10 mm Hg, p = 0.003), D/S ratio (0.563 ± 0.044-0.538 ± 0.031, p = 0.006), and eGFR (92 ± 20-84 ± 24 mL/min/1.73 m2, p = 0.003). Discussion/Conclusion: In conclusion, in patients with SSc complicated by digital ulcers and normal to mildly diminished kidney function, bosentan had no effect on intrarenal hemodynamics, but reduced blood pressure levels and kidney function.